4D-printed bi-material composite laminate for manufacturing reversible shape-change structures. (15th August 2021) - Wang, Yanan; Li, Xiang
Abstract: Reversible deformable structures manufactured by four-dimensional (4D) printing have potential applications in numerous fields, such as actuators, intelligent mechanisms, and soft robots. In this study, a novel low-cost approach for realizing reversible structural deformation by fused deposition modeling (FDM) 4D printing is proposed, which combines the thermodynamic properties of an elastomer material (thermoplastic polyurethane, TPU) and a shape-memory material (polylactic acid, PLA). PLA with stored pre-strain (which has a storage modulus that changes greatly with temperature) was used as the active layer, while TPU (which has a stable storage modulus) was used as the passive layer. A mathematical model was established to analyze the versatility of this combination of materials and clarify the requirements of the related materials. The experimental deformation results of the composite laminate structures (whose properties were controlled by the printing parameters and structural parameters) were consistent with the simulation results, and the deformation trends were consistent with the trends obtained by the mathematical model. A variety of models were manufactured using the composite laminate, which can realize reversible complex deformation with simulation pre-programming. This strategy is scalable, and the basic design principles have broad application prospects in reversible 4D printing.